Automation of QIIME2 Metagenomic Analysis Platform. Issue 9 (23rd September 2021) - Fung, Calvin; Rusling, Mathew; Lampeter, Thomas; Love, Charles; Karim, Anisha; Bongiorno, Christian; Yuan, Li‐Lian
Abstract: QIIME is a widely used, open‐source microbiome analysis software package that converts raw sequence data into interpretable visualizations and statistical results. QIIME2 has recently succeeded QIIME1, becoming the most updated platform. The protocols in this article describe our effort in automating core functions of QIIME2, using datasets available at docs.qiime2.org . While these specific examples are microbial 16S rRNA gene sequences, our automation can be easily applied to other types of QIIME2 analysis. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparing files and folders Support Protocol 1 : Preparing your data for QAP Support Protocol 2 : Understanding automated options Basic Protocol 2 : Importing into QIIME Basic Protocol 3 : DADA2: Filtering, trimming, merging pairs Basic Protocol 4 : Performing core metrics Basic Protocol 5 : Sample filtering by metadata Basic Protocol 6 : Alpha diversity metrics Basic Protocol 7 : Cross‐sectional beta diversity Basic Protocol 8 : Longitudinal feature volatility Basic Protocol 9 : Sample classification